2015
DOI: 10.1214/15-ejs1067
|View full text |Cite
|
Sign up to set email alerts
|

Survey questionnaires and graphs

Abstract: We introduce a special type of graphs, which we use as tools for designing and improving survey questionnaires. While the idea of representing questionnaires as graphs is not new, our graphs constitute novel theoretical and practical tools, which could turn a complex questionnaire into a questionnaire that is easier to visualize, test and analyze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…We were not familiar with Depth First Search at the time, discovering only later that the structural paths algorithm is a variation on a fundamental algorithm in computer science (Knuth, 1997). Schiopu-Kratina et al (2015) is the most recent publication we have found on this subject. They cite (Picard, 1965) as the pioneer, but state that his work has not yet been applied and suggest reasons for this.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We were not familiar with Depth First Search at the time, discovering only later that the structural paths algorithm is a variation on a fundamental algorithm in computer science (Knuth, 1997). Schiopu-Kratina et al (2015) is the most recent publication we have found on this subject. They cite (Picard, 1965) as the pioneer, but state that his work has not yet been applied and suggest reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of these works is complicated by different terminology, different approaches, and different objectives. What we refer to as BEGIN and END are referred to as "source" and "sink" by Fagan and Greenberg (1988, 3), as "start vertex" and "end vertex" by Bethlehem and Hundepool (2004, 242), and as "root" and "terminal" by Schiopu-Kratina et al (2015, 2207. Our structural and valid paths are "logically possible routes" and "incorrect routes" in Bethlehem and Hundepool (2004, 253).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations